PENGARUH PERMAINAN SUKU MANDAILING INGKE-INGKE TERHADAP LOMPAT JAUH PADA SISWA KELAS 4 SD DI SEKOLAH BUDISATRIYA - laila Hidayati Lubis; Khairul Usman; Robenhart Tamba; Try Wahyu Purnomo; Winara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Mandailing tribe game ingke-ingke on the long jump of 4th grade elementary school students at Budisatriya School. The background of this study departs from the still minimal use of learning media that utilize traditional games. Therefore, this study focuses primarily on the development of learning materials for basic jumping movements through the traditional game ingke-ingke. The research method used in this study is an experimental method using a quasi-experimental research model using quantitative data analysis. The results of the study indicate that the developed learning media has gone through various stages of testing, starting from the normality test, homogeneity test and hypothesis test. Based on the results of the normality test, a normality test was conducted to determine whether the data used were normally distributed. Next, a homogeneity test was conducted to determine whether the variance between the research data groups was homogeneous. Finally, a homogeneity test was conducted to determine whether there was an effect of a previously administered treatment. Overall, the developed media proved to be highly valid, practical, and highly effective as a learning tool.